2012
DOI: 10.1002/cncy.20203
|View full text |Cite
|
Sign up to set email alerts
|

Cervical screening in England: The past, present, and future

Abstract: *Cervical screening in England commenced in a disorganized fashion in 1964. The flaws of this approach became apparent in the mid-1980s and led to the inception of the National Health Service Cervical Screening Programme (NHSCSP). The main features of this program are its population-based registry, accessibility to all women within the screening age range, its systematic process of call and recall, national coordination, and quality assurance. Its success is in part based on its ability to evolve as evidence n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 37 publications
(33 reference statements)
0
45
0
Order By: Relevance
“…Cervical screening programmes in the UK are based on LBC and high grade HPV molecular testing. The authors of the programme observed dynamic changes in the number of the women vaccinated against HPV, as well as cultural and social changes imposing alternation of the existing patterns [9,10]. Similar conclusions regarding the changes in screening patterns were made by Norwegian scientific researchers.…”
Section: Risk Factorsmentioning
confidence: 70%
See 1 more Smart Citation
“…Cervical screening programmes in the UK are based on LBC and high grade HPV molecular testing. The authors of the programme observed dynamic changes in the number of the women vaccinated against HPV, as well as cultural and social changes imposing alternation of the existing patterns [9,10]. Similar conclusions regarding the changes in screening patterns were made by Norwegian scientific researchers.…”
Section: Risk Factorsmentioning
confidence: 70%
“…Since the efficiency of the programmes differs in many countries, although similar methods are used, the assumption can be made that the reason for poor cervical cancer diagnosis in most countries is women's poor knowledge of carcinogenic and cancer risk factors [5][6][7][8][9]. The statistics in Poland during the period 2000-2009 show a decrease in the total number of cancer diagnoses in 3100 cases out of 3800 annually.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent HPV infection after treatment predicts the risk of disease recurrence or invasive cancer; therefore, HPV test can be used for follow-up of treated women. Evidences from several follow-up studies suggest that women negative for both cytology and HPV test at 6-12 months follow-up may be considered Bcured^and can be sent back to routine screening and rescreened after 3 years [51,52]. A systematic review of the studies about the performance of HPV test in posttreatment follow-up shows that the test is significantly more sensitive (95 %) as compared to follow-up cytology (70 %) in detecting persistent/recurrent high-grade lesions [53].…”
Section: Role Of Hpv Test In Posttreatment Follow-upmentioning
confidence: 99%
“…Many countries have commenced with ad hoc screening offered and taken up by a few, followed by a wider policy of promoting opportunistic screening, and eventually by the development and implementation of a national or regional 'organised' screening programme [1][2][3][4][5]. It is widely held that organised programmes are more effective than non-organised, or opportunistic, screening programmes in preventing cervical cancer, and it is well recognised that organised cervical screening reduces cervical cancer incidence and mortality [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%